Combined use of remote sensing and geostatistical data sets for estimating the dynamics of shortwave radiation of bare arable soils in Europe. Issue 5 (19th March 2019) - Cierniewski, Jerzy; Ceglarek, Jakub; Kaźmierowski, Cezary; Roujean, Jean-Louis
ABSTRACT: Smoothing rough ploughed soils increases their albedo, which results in a lower amount of shortwave radiation being absorbed by their surface layer. That surface emits less longwave radiation, leading to a reduction in its temperature, which in turn can affect the climate. This article presents a multistage procedure using remote sensing and geostatistical data sets for quantification of the annual dynamics of shortwave radiation reflected from air-dried bare soils within arable lands of the European Union and its associated countries, Norway and Switzerland. The soils, being cultivated under conventional tillage, were treated as bare formed by a plough (Pd) and a smoothing harrow (Hs), when the major crops were planted there. Information about the areas of the soils and periods when they are bare was obtained from vectorized and rasterized geostatistical data sets. The spatial diversity of the spectral reflectance of the soils, characterized by thousands of their reflectance spectra (stored in the European Land Use and Cover Area frame Survey Top Soil Database), were used to predict the half-diurnal albedo variation of the soils on a given day of the year. The shortwave radiation reaching the examined soils was obtained from satellite data of the Spinning Enhanced Visible and Infrared Imager instrument. It was found that the maximum radiation levels reflected from the soils occur between the beginning of April and the end of May. During these periods, the radiation reflected from the soils formed by Pd and Hs can reach about 220 and 250 PJ d −1 in the western part of the EU, 150 and 190 PJ d −1 in the central part, and up to 280 and 330 PJ d −1 in the southern part.